PERBEDAAN EFEK IMPLEMENTASI BOOKLET DAN MANEKIN PADA PENYULUHAN KEBUTUHAN PERSONAL HIGIENE GENETALIA DI SDN RONOWIJAYAN KABUPATEN PONOROGO JAWA TIMUR - Fitriani, Inna Sholicha; Rosyadia, Fetty (Universitas Tribhuwana Tunggadewi, 2020)
Adolescence is a period of maturity of human reproductive organs. Candidiasis 25 % - 50 %, vaginitis 20% - 40% and trichomoniasis 5% - 15%. Every teenager must have the right and proper information about reproductive health aspects such as how to maintain the health of reproductive organs, and be able to practice the behavior of maintaining healthy and responsible reproductive organs to avoid diseases that might attack their reproductive organs. This study aims to identify the differences in the effects of the implementation of booklets and mannequins on counseling the personal needs of genetalia hygiene in young women at Ronowijayan Ponorogo Elementary School. This study used an experimental method with a type of randomized experimental study. The research location was the SDN Ronowijayan Siman Ponorogo period of study starting in February December 2018. The study population used was all young women at Ronowijayan Ponorogo Elementary School with a study sample aged 10 untill 12 years at Ronowijayan Ponorogo Elementary School. The results of the data were analyzed using the T test (α = 5%) with the normality test of the distribution using Shapiro-Wilk. The results of the study were 0.896> 0.05 (95% confidence), so there was no difference in effect between before treatment and after treatment of the implementation of the booklet with the implementation of manikin. It is necessary to introduce reproductive health with a family approach method for young women with the hope that the achievement of reproductive health education can be achieved optimally.